Pengaruh Kepemimpinan, Komunikasi Organisasi, Motivasi Kerja, terhadap Kinerja Pegawai di Lingkungan Kantor Kementerian Agama Provinsi Lampung - Sumaryati; Mahdum Kholit Al-Asror (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
Efforts to improve employee performance can be done in various ways, one of them is by preparing employees who are professional, competent and high-performing. Employee performance in the office of the Ministry of Religion of Lampung Province is influenced by various factors, namely the contribution of leadership, organizational communication and work motivation. This research was carried out using a quantitative approach and descriptive survey method. The population is employees in offices of the Ministry of Religion of Lampung Province, totaling 2,219 employees. The sample in this study was 10%, namely 200 employees. The research data was collected through questionnaires and analyzed using descriptive statistical techniques and path analysis. Based on the data obtained and researched and tested it can be concluded as follows: 1) Leadership influences organizational communication. 2) Leadership influences work motivation. This shows that leadership and work motivation are in line with perceptions of employee performance. 3) Organizational communication has little effect on work motivation. This shows that organizational communication is less effective and efficient so that it is not in line with perceptions of employee performance. 4) Leadership influences employee performance. This shows that there is consistency between leadership and the performance of employees from the leadership. 5) Organizational communication has little effect on employee performance. This means that the lack of communication from a leader to employees can reduce the productivity of performance and performance of employees. 6) work motivation affects employee performance.